Synthesis and Cytotoxic Activity of Novel 3-methyl-1-[(4-substitutedpiperazin-1-yl)methyl]-1H-indole Derivatives - Koksal, M.; Yarim, M.; Durmaz, I.; Cetin-Atalay, R. (Arzneimittelforschung, 2012)
A series of novel 3-methyl-1-[(4-substitutedpiperazin-1-yl)methyl]-1H-indoles (3a–l) were synthesized and their cytotoxicities were analyzed against 3 different human cell lines, including liver (HUH7), breast (MCF7) and colon (HCT116). The Mannich reaction of 3-methylindole (1) with 4-substitutedpiperazines (2) and formaldehyde resulted to the 3-methyl-1-[(4-substitutedpiperazin-1-yl)methyl]-1H-indoles (3a–l) in 38–69% yields. The investigation of anticancer screening revealed that the tested compounds showed comparable activity to the reference drug 5-fluorouracil and compounds 3g, 3h, 3i and 3k, had lower 50% inhibition (IC50) concentration than reference drug. Moreover, the cytotoxic effect of the most potent compound 3h on HUH7 and MCF7 cells through apoptosis was visualized by Hoechst staining and compared with paclitaxel, which is a mitotic inhibitor acting on microtubules. The morphological features of apoptosis were observed as condensed and fragmented nuclei that are similar to paclitaxel.
Keywords: anticancer; apoptosis; indole; Mannich base; 1,4-disubstitutedpiperazines